Perceptions of learning and perceptions of being taught: Adult learner reactions to an interactive website - Toynton, Bob (Proceedings of the International Conference on Networked Learning, 2002)
This study examines the reactions of a group of adult learners to an interactive website. Through questionnaires and semi-structured interviews, answers were sought to the roles of recognised prior knowledge and tacit knowledge in both intentional and incidental learning within this medium. Previous experience of the medium appears to have little influence on the perceptions of teaching and learning. However, the extent of the learners' pre-knowledge of the subject matter addressed within the site may be important to their perception of the learning environment. This influences their perceptions of what is relevant knowledge and their recognition of knowledge acquisition. That those with most prior knowledge initially failed to recognise learning is explained within a constructivist context. The need to consider the range, and the effects of the range, of adult learner prior knowledge when designing interactive websites is illustrated.